2022
DOI: 10.1111/cge.14254
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant in AFF3 underlying isolated syndactyly

Abstract: Isolated syndactyly is a common limb malformation with limited known genetic etiology. We used exome sequencing to discover a novel heterozygous missense variant c.2915G > C: p.Arg972Pro in AFF3 on chromosome 2q11.2 in a family with isolated syndactyly in hands and feet. AFF3 belongs to a family of nuclear transcription activating factors and is involved in limb dorsoventral patterning. The variant Arg972Pro is located near the C terminus, a region that is yet to be associated with human disorders. Functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We previously showed that overexpression in zebrafish embryos of human AFF3 leads to a dose-dependent increase of developmental anomalies 11 , a phenotype that was further exacerbated upon overexpression of the p.(Ala233Thr) KINSSHIP isoform 49 . To assess the pathogenicity of the missense variants identified in the biallelic individuals, we injected zebrafish with human AFF3 mRNA wild-type (Wt), two selected missense variants present in homozygous state in probands B1 and B2 and his affected sister B3 and mapping outside of crystalized domains (Lys528Arg and Thr594Ser), two KINSSHIP variants (Ala233Thr and Val235Gly) and as control Gln179Glu (Chr2 (GRCh37) g.100623432:G>C, c.535C>G), a variant not described in GnomAD, we identified in homozygosity in a healthy individual.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that overexpression in zebrafish embryos of human AFF3 leads to a dose-dependent increase of developmental anomalies 11 , a phenotype that was further exacerbated upon overexpression of the p.(Ala233Thr) KINSSHIP isoform 49 . To assess the pathogenicity of the missense variants identified in the biallelic individuals, we injected zebrafish with human AFF3 mRNA wild-type (Wt), two selected missense variants present in homozygous state in probands B1 and B2 and his affected sister B3 and mapping outside of crystalized domains (Lys528Arg and Thr594Ser), two KINSSHIP variants (Ala233Thr and Val235Gly) and as control Gln179Glu (Chr2 (GRCh37) g.100623432:G>C, c.535C>G), a variant not described in GnomAD, we identified in homozygosity in a healthy individual.…”
Section: Resultsmentioning
confidence: 99%
“…The de novo missense identified in individuals M1 and M2 are shown in green. While the p.(Arg947Pro) shown in black was shown to segregate with isolated syndactyly 49 ., we have also identified it in individuals with no digit abnormalities. (B) UCSC genome browser snapshot of the Chr2 99.5 to 101.4 Mb region showing the genes mapping to this interval.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the structure of the SIAH1–AFF3 degron interface suggests the impairment of their mutual binding (Figure 1D). Very Recently, a heterozygous missense variant outside the degron (NM_001025108.2:c.2915G>C p.Arg972Pro) was detected in a family with non‐syndromic syndactyly 10 . Three patients from this family showed no ID nor KINSSHIP syndrome, implying a possible genotype–phenotype correlation.…”
Section: Discussionmentioning
confidence: 96%
“…4,8,9 Upon the overexpression of AFF3 in zebrafish, body axis anomalies were identified, providing some support for the pathological effect of an excess of AFF3 mRNA. 4,10 Clustered missense variants in the degron region strongly indicated its importance to the disease pathogenesis, although the nature of the pathogenesis of KINSSHIP syndrome is still elusive. Similarly, CHOPS syndrome arises from missense variants in the degron of AFF4 disrupting its interaction with SIAH1, preventing SEC degradation, and thus leading to the abnormal expression of genes due to the continued existence of the SEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation